Cytotoxicity Study of Composite Restorative Materials in Dentistry - Murdiyanto, Dendy; Kartinawati, Arny Try; Larezha, Dannu (Prosiding University Research Colloquium, 2022)
Composite resin is one of the dental restorative materials that is currently often used in dental practice. Composite resin is currently widely used for restoration because it has a color that almost resembles the color of natural teeth so that it will produce a very satisfying aesthetic. However, composite resins also have several disadvantages, including cytotoxicity. This literature review aims to determine whether dental composite resin restoration materials are cytotoxic. Methacrylate-based resin monomers such as Bis-GMA, TEGDMA, and UDMA are cytotoxic. Incomplete polymerization of composite resins can produce residual monomers that will come into contact with the oral environment and can cause irritation to the soft tissues of the oral cavity and also the pulp. The composite resin monomer has cytotoxicity. The order of the most cytotoxic composite resin monomers was Bis-GMA > UDMA > TEGDMA